Institutions and markets in India's development essays for K N Raj - Vaidyanathan A ed.; National Conference in honor of K N Raj; National conference in honor of K N Raj Kerala, India 2-3 Oct 2004 (New Delhi OUP, 2007)
It deals with several aspects of the Indian economy from independence till date. Macro-economy section examines shifts in the economic policy paradigm, quest for inclusive growth, sources of economic growth, and macroeconomic puzzles in the past decade. The 2nd section reviews the preference for land, Indiats savings performance since 1950 & recent technology policy initiatives. Industrial growth in India and China, agriculturetindustry interactions & the sacred cow controversy are discussed in section 3. The 4th section analyses strategies for labour movement and conceptual and measurement issues relating to employment and unemployment in developing countries, as well as growth of work opportunities in India. The In last part Kerala Model of Development and the factors behind the statets growth, as well as the outcomes of Democratic Decentralization in some other states are discussed
Keywords: Raj, K. N. (Kakkadan Nandanath); Central planning; Economic development projects; India